A unique case of two primaries: carcinoma breast with carcinoma gallbladder - Pogal, Jaipalreddy (BMJ Publishing Group, 2013)
The presence of two primary cancers in a patient is a very rare entity. Carcinoma breast and carcinoma gallbladder are one of the commonest cancers in North Indian women. We report a unique case of carcinoma breast with synchronous primary cancer in gallbladder. A 52-year-old woman presented with a lump in her left breast since 6 months. On examination, the lump was malignant with the involvement of the overlying skin and ipsilateral axillary lymphadenopathy. She also had hepatomegaly with palpable gallbladder lump. On imaging, there was a gallbladder mass infiltrating the adjacent organs. Biopsy of the breast lump revealed infiltrating ductal carcinoma, which was oestrogen, progesterone and HER-2 neu receptor positive. Immunohistochemistry analysis using cytokeratin 7 and 20 on gallbladder and breast mass biopsy specimen revealed the presence of separate primary cancers of gallbladder and breast. The patient received palliative chemotherapy, but died of the disease 5 months after diagnosis.